CO-BRANDING STRATEGY BETWEEN AZARINE AND MARVEL TO INCREASE PRODUCT SALES - Hardiyanti, Marsa Faaiza; S.Sos., M.I.Kom., Mutiah, (The Commercium, 2024)
Co-branding strategies have become a popular approach for companies to increase the visibility and sales of their products by leveraging the strength of established brands. In this context, this research explores the collaboration between Azarine, a leading cosmetics brand, and Marvel, an entertainment company widely known for its iconic superhero characters. This research aims to analyze the co-branding strategy used by Azarine and Marvel and its impact on product sales. The research method used is case analysis by collecting data from various sources including interviews with company management and consumer surveys. The analysis results show that the collaboration between Azarine and Marvel has succeeded in creating unique cosmetic products with a superhero theme that are liked by fans of both brands. Integrated marketing strategies, including social media campaigns, advertising, and promotional appearances at special events, have been effective in increasing brand awareness and consumer interest.